THE FAMILY RELATIONSHIP BETWEEN SABU, ROTE, TETUN AND LAMAHOLOT LANGUAGES - Lanny I.D. Koroh (International Conference on Languages and Arts, 2014)
This article contains a description of the results of research on the family relationship among Sabu Language (SL), Rote Language (RL), Tetun Language (TL), and Lamaholot language (LL). Based on the concept and glotocronology lexicostatistic, this study successfully reveals social relationships among those four languages, which are determined based on the computation of relative vocabulary and year split. This quantitative analysis presents the level of relationship closeness among SL, RL, TL, and LL, as follows: level relationship closeness between RL and TL of 24.5%; between SL and RL of 17.5%; between TL and LL of 17%; between SL and TL and between RL and LL, respectively 15%; and between SL and LL of 12.5%. Based on pedigree kinship dwipilah technique, it can be concluded that PSRTL (Proto Sabu-Rote-Tetun-Lamaholot) yields RL and LL. In the process of becoming RL, SL and TL emerge. Thus, the closeness of the relationship among the four languages ​​can be sorted as follows (from the closest one): RL-TL, RL, SL, TL, LL, SL, TL / RL-LL, and SL-LL. This proportional relationship closeness sequence with detachable years; closer social ties, more youthful-year split, on the contrary, the more distant kinship relationships, grow older year split. Keywords: language kinship, relationship closeness, genealogical kinship, year split.